RESEARCH OF CAVITATION EROSION OF STRUCTURAL MATERIALS - Tarasenko, Taras; Badakh, Valery; Syvashenko , Terentiy (Problems of Friction and Wear, 2023)
The results of experimental studies of the patterns of wearing of structural materials which are used in the hydraulic machine design engineering under the impact of hydrodynamic cavitation are presented. It is proposed to use a throttle device working in the mode of developed cavitation and being the throttle generator of cavitation pressure fluctuations, as a cavitation generator in studies of the cavitation resistance of structural materials. The rational type of throttling device for creating the liquid’s cavitation flow has been established based on the analysis of flow and differential characteristics of throttling devices of various schemes, which work as throttle cavitation generators of pressure fluctuations. It is proposed to use the dimensionless pressure drop on the throttle cavitation generator of pressure fluctuations as a cavitation criterion. The peculiarities of generation of the cavitation pressure oscillations by a throttle generator have been studied. The regularity of the influence of the pressure drop on the throttle cavitation generator of pressure fluctuations (mode of operation) on the range of cavitation pressure fluctuations and the amount of cavitation wear has been established. The influence of the geometric parameters of the throttle cavitation generator of pressure fluctuations on the intensity of the cavitation erosion was determined. Analytical dependences of the rate of cavitation erosion of test samples of materials on the pressure at the inlet to the throttle cavitation generator of pressure fluctuations were determined. The results of the experimental research can be used to create highly efficient throttle cavitation generators of pressure fluctuations for the study of the cavitation erosion, cleaning the parts from contamination, intensification of technological processes in the chemical, oil production and other industries. On the other hand, the obtained results make it possible to create the hydraulic units that will have the high resistance to the cavitation erosion.